Analisis Kesalahan Mahasiswa dalam Menyelesaikan Soal Persamaan Garis Lurus - Haryadi, Rahman; Nurmaningsih, Nurmaningsih (Universitas Hamzanwadi, 2019)
The purpose of this research is to know the mistakes made by students of Program Studi Pendidikan Matematika in solving the equation of straight line problem. This research was conducted in Program Studi Pendidikan Matematika IKIP-PGRI Pontianak in the odd semester of Academic Year 2017/2018. This research uses a descriptive method with research form is a case study. The subject of his research is the third-semester students who have studied the equation of straight line material. The results of this study indicate that systematic errors are as many as 18 errors or equal to 47.37%, random error that is as much as 3 errors or equal to 7.89%, mistake carelessness as much as 17 mistakes or by 44, 74%.